Electrode material comprising silicon oxide and single-walled carbon nanotubes

The electrode material with alkali metal silicate and SWCNTs, encapsulated in a flexible graphene coating, addresses the mechanical and electrical challenges of silicon-based anodes, improving cycle life and energy density in lithium-ion batteries.

KR103042467B1Active Publication Date: 2026-11-05NANOGRAF CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020237004706
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-14
Filing Date
2021-07-14
Publication Date
2026-11-05
Estimated Expiration
2041-07-14

AI Technical Summary

Technical Problem

Current lithium-ion battery anode materials, particularly those based on silicon, suffer from poor cycle life due to mechanical stress and electrical disconnection caused by large volume expansion during lithiation, leading to low Coulomb efficiency and capacity loss.

Method used

An electrode material comprising active material particles made of alkali metal or alkaline earth metal silicate and single-walled carbon nanotubes (SWCNTs) is developed, with a specific composition that includes a flexible, highly conductive graphene coating to encapsulate the core particles, providing long-range conductivity and maintaining mechanical and electronic integrity.

Benefits of technology

The proposed electrode material enhances cycle life stability and maintains high energy density by minimizing particle fragmentation and ensuring continuous electrical contact, despite the inherent expansion associated with lithium storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112023015104493-PCT00015_ABST
    Figure 112023015104493-PCT00015_ABST
Patent Text Reader

Abstract

The electrode material for a lithium-ion secondary battery comprises active material particles containing alkali metal or alkaline earth metal silicates, a binder, and single-walled carbon nanotubes (SWCNTs).
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electrode material comprising silicon oxide and single-walled carbon nanotubes (SWCNTs), and in particular to an anode comprising said electrode material and a lithium-ion battery comprising said anode. Background Technology

[0002] Lithium (Li) ion electrochemical batteries generally require materials that enable high energy density, high power density, and high cycle stability. Lithium-ion batteries are commonly used in a wide range of applications, including consumer electronics, wearable computing devices, military mobile equipment, satellite communications, spacecraft devices, and electric vehicles; they are particularly widely used in large-scale energy applications such as low-emission electric vehicles, renewable power plants, and stationary electric grids. Furthermore, lithium-ion batteries are at the forefront of next-generation wireless and portable communication applications. One or more lithium-ion batteries can be used to construct a battery that serves as the power source for these applications. However, what is accelerating research into lithium-ion batteries with much higher energy density, higher power density, faster charge-discharge rates, and longer cycle life is the explosive increase in the number of applications requiring more energy. Additionally, as the adoption of lithium-ion technology increases and applications shift toward higher current requirements, longer run times, wider and higher power ranges, and smaller form factors, the need to scale up today's energy and power densities continues to grow.

[0003] Active anode materials such as silicon are currently considered desirable alternatives to graphite-based anodes due to their high lithium storage capacity (up to 3200 mAh / g), which can exceed seven times that of graphite. However, due to the large volume expansion of alloy particles upon lithiation, these anode materials generally have very poor cycle life due to mechanical stress, low Coulomb efficiency, and electrical disconnection.

[0004] Therefore, there is a need for an advanced anode active material for use in electrochemical cells that incorporates a carbon material of defined quality characteristics that favorably influences the cyclicity of the electrochemical cell.

[0005] One embodiment of the present invention provides an electrode material for a lithium-ion secondary battery comprising active material particles comprising an alkali metal or alkaline earth metal silicate, a binder, and single-walled carbon nanotubes (SWCNT). In one embodiment, the electrode material comprises, based on the total weight of the electrode material, a combination of graphite particles and metal silicate particles of at least about 80 weight%, a binder of about 1 weight% to about 5 weight%, and single-walled carbon nanotubes (SWCNT) of about 0.05 weight% to about 1 weight%. Brief explanation of the drawing

[0006] FIG. 1a is a scanning electron microscope (SEM) image of an active material composite particle according to various embodiments of the present disclosure, and FIG. 1b to 1d are cross-sectional views of a core particle that may be included in the composite particle of FIG. 1a. Figures 2a, 2b, and 2c show the Raman spectra for graphite and various graphene-based materials. Figure 3 shows the Raman spectra of a typical carbon material and low-defect turbostratic carbon I D / I G It is a bar graph comparing ratios. Figures 4a, 4b, and 4c show the Raman spectra of electrode active materials comprising core particles encapsulated in amorphous carbon, reduced graphene oxide (rGO), and low-defection non-defective carbon, respectively. FIGS. 5a and 5b are schematic cross-sectional views of a portion of the anode electrode of an example in a manufactured state and after repeated charge-discharge cycles, respectively. Figures 6a, 6b, and 6c are graphs illustrating the capacity retention of half-cells of the examples and comparative examples. Specific details for implementing the invention

[0007] Various embodiments are described in detail below with reference to the attached drawings. Where possible, the same reference numbers are used throughout the drawings to indicate identical or similar parts. References to specific embodiments and implementations are for illustrative purposes only and are not intended to limit the invention or the claims.

[0008] When a component or layer is referred to as being "on" or "connected to" another component or layer, it may be directly on, directly connected to, or an intermediate component or layer may exist. In contrast, when a component is referred to as being "directly on" or "directly connected" to another component or layer, no intermediate component or layer exists. For the purposes of this disclosure, it will be understood that "at least one of X, Y, and Z" may be interpreted as X alone, Y alone, Z alone, or any combination of two or more items X, Y, and Z (e.g., XYZ, XYY, YZ, ZZ).

[0009] Where a range of values ​​is provided, unless otherwise specified in the context, the upper and lower limits of such range and each intermediate value up to one-tenth of the unit of the lower limit between any other mentioned or intermediate value within the described range are included in the invention. The upper and lower limits of such smaller ranges may independently be included in smaller ranges, which are also included in the invention, subject to any specifically excluded limits in the described ranges. Where a described range includes one or both of the limits, a range excluding one or both of the included limits is also included in the invention. Additionally, the term "about" will be understood to refer to a small measurement error, for example, of + / - 5% to 10%.

[0010] Words such as "thereafter," "then," and "next" are not necessarily intended to restrict the order of steps. These words may be used to guide the reader through the description of the method. Furthermore, referring to a claim component in the singular using, for example, the articles "a," "an," or "the" should not be interpreted as restricting the component to the singular form.

[0011] "Electrode material" is defined as a material that can be configured to be used as an electrode in an electrochemical cell, such as a lithium-ion rechargeable battery. "Electrode" is defined as the anode or cathode of an electrochemical cell. "Composite electrode material" is also defined as comprising active material particles combined with one of particles, flakes, spheres, platelets, sheets, tubes, fibers, or combinations thereof that are electrically conductive materials. The particles, flakes, spheres, platelets, sheets, tubes, fibers, or combinations thereof may also be flat, crumpled, wrinkled, layered, woven, braided, or a combination thereof.

[0012] The electrically conductive material may be selected from the group consisting of: electrically conductive carbon-based materials, electrically conductive polymers, graphite, metal powders, nickel, aluminum, titanium, stainless steel, and combinations thereof. The electrically conductive carbon-based material may further comprise: graphite, graphene, diamond, pyrolytic graphite, carbon black, low-defect non-stratified carbon, fullerene, or combinations thereof. The “electrode material mixture” is defined as a combination of the following materials: material particles (electrochemically active, electrically conductive, composites, or combinations thereof), a binder or binders, and a non-crosslinked and / or crosslinked polymer or polymer that is mixed together for use in forming an electrode for an electrochemical cell. In this specification, “electrochemically active material,” “electrode active material,” or “active material” is defined as a material that stores and releases potential by inserting and releasing ions, such as ions in an electrolyte. The terms “insertion and release” may further be understood as intercalates and deintercalates, or ions that are lithiated and delithiated. Therefore, the processes of ion insertion and release are understood as intercalation and deintercalation, or lithiation and delithiation. Accordingly, "active material," "electrochemical active material," or "active material particle" is defined as a material or particle capable of repeating ion intercalation and deintercalation, or lithium lithiation and delithiation.

[0013] As defined herein, a secondary electrochemical cell is a rechargeable electrochemical cell or battery. Here, "capacity" is defined as a measure of the charge stored in the battery, determined by the mass of the active material contained within the battery, representing the maximum amount of energy in ampere-hours (Ah) that can be extracted from the battery at the rated voltage. Capacity may also be defined by the following equation: Capacity = Energy / Voltage, or Current (A) x Time (h). "Energy" is mathematically defined by the following equation: Energy = Capacity (Ah) x Voltage (V). "Specific capacity" is defined herein as the amount of charge that can be delivered per unit of mass or volume of the active electrode material for a specific time. Specific capacity may be measured in units of weight, such as (Ah) / g, or units of volume, such as (Ah) / cc. Specific capacity is defined by the following mathematical equation: Specific capacity (Ah / kg) = Capacity (Ah) / Mass (kg). "Rate capability" is the ability of an electrochemical cell to receive or deliver a certain amount of energy within a specific period. Alternatively, "rate capability" is the maximum continuous or pulsed energy that a battery can provide per unit of time.

[0014] "C-rate" is defined herein as a measure of the rate at which a battery is discharged relative to its maximum nominal capacity. For example, a 1C current rate means that the discharge current discharges the entire battery within 1 hour. A C / 2 current rate means that the battery is fully discharged within 2 hours, and a 2C current rate means that the battery is fully discharged within 0.5 hours. "Power" is defined as the rate of energy transfer time measured in watts (W). Power is the product of the voltage (V) of the battery or cell and the current (A) passing through the battery or cell. The "C-rate" is mathematically defined as C-Rate (Inverse Time) = Current (A) / Capacity (Ah) or C-Rate (Inverse Time) = 1 / Discharge Time (h). Power is defined by the following mathematical equation: Power (W) = Energy (Wh) / Time (h), or Power (W) = Current (A) x Voltage (V). Coulomb efficiency is the efficiency of charge transfer within an electrochemical cell. Coulomb efficiency is the ratio of the battery's charge output to its charge input.

[0015] Significant developments in both commercial and academic settings have focused on designing systems that minimize or accommodate the total volume swelling of alloy particles and associated electrochemical losses. This has generally been approached from two perspectives: at the particle level, designing particle structures that confine expansion to small domains to prevent particle breakage and electrical discontinuity; and at the electrode level, designing polymer matrices and conductive networks capable of accommodating the volume swelling of lithium storage materials while maintaining mechanical and electronic integrity during the repeated charge / discharge operation of lithium-ion batteries.

[0016] For example, a popular technique for stabilizing the cycle life of alloy active anode materials, such as silicon, involves utilizing mixing, encapsulation, or other integration with various carbon materials to provide electronically conductive surfaces and facilitate general electronic conduction throughout the electrode particle network. This includes CVD amorphous carbon coating, graphene wrapping, and physical mixing with graphite, conductive carbon, and carbon nanoplatelets. However, the active material can still swell due to its rigid properties and lack of long-range order, and the particles may remain isolated, leading to storage capacity loss and lithium trapping.

[0017] Various embodiments of the present disclosure provide an anode material for a lithium-ion battery comprising active material particles comprising alkali metal or alkaline earth metal silicates, and single-walled carbon nanotubes (SWCNTs) providing long-range conductivity in a network of active material particles, which can increase the stability of the cycle life despite the inherent expansion associated with lithium storage metal alloy particles.

[0018] SiO material

[0019] Silicon and silicon alloys can significantly increase cell capacity when included within the electrodes of an electrochemical cell. Silicon and silicon alloys are often incorporated within electrodes containing graphite, graphene, or other carbon-based active materials. Examples of electrodes containing carbon-based materials and silicon are provided in U.S. Patents 8,551,650, 8,778,538, and 9,728,773 (inventors Kung et al.) and U.S. Patents 10,135,059 and 10,135,063 (inventors Huang et al.), all of which are fully incorporated herein by reference.

[0020] Here, "SiO" materials can refer to silicon and oxygen-containing materials. Interest is focused on using SiO materials as anode electrodes in lithium-ion batteries due to their high theoretical energy and power densities. However, currently commercialized SiO materials have faced limitations in utilization due to their low primary cycle efficiency and high irreversibility. This low primary cycle efficiency is attributed to the high irreversible Li+ reaction with the SiO matrix.

[0021] To reduce the irreversible Li+ reaction with silicon oxide, various embodiments include a metallized silicon oxide material (M-SiO). Here, the M-SiO material may refer to an active material that reacts directly with a metal-containing precursor, such as an alkali and / or alkaline earth metal-containing precursor, such as a lithium-containing precursor and / or a magnesium-containing precursor, to form a metallized silicon and oxygen-containing phase before being used as an active material in a battery and / or undergoing charge and discharge reactions. In one embodiment, all or part of the metallized metal may remain in the active material and is not intercalated (i.e., not inserted) or deintercalated during battery charge and discharge. However, in some embodiments, the M-SiO material may include a SiO material metallized to include other suitable alkali and / or alkaline earth metals, such as sodium, potassium, calcium, etc. For example, in some embodiments, the M-SiO material may be metallized to include magnesium, lithium, sodium, potassium, calcium, or any combination thereof. Preferably, the M-SiO material may refer to a lithium metallized SiO (LM-SiO) material and / or an Mg metallized SiO (MM-SiO) material.

[0022] Electrode materials containing M-SiO active materials have been found to provide increased first-cycle efficiency (FCE) compared to non-metallic SiO materials. Unfortunately, M-SiO materials suffer from severe electrical discontinuity and rapid capacity loss, which often leads to capacity fade of over 90% within 20 cycles. Coating M-SiO materials with carbon and / or other materials, or mixing M-SiO materials with graphite, has been found to slightly reduce the electrical discontinuity and capacity loss of the active material, delaying capacity fade of over 50% to approximately 50 cycles, which is still very unsatisfactory cyclic stability for commercial applications. Overall, current M-SiO materials do not exhibit sufficient electrical stability for commercialization.

[0023] FIG. 1a is a scanning electron microscope (SEM) image of an active material particle (100) according to various embodiments of the present invention, and FIG. 1b to 1d are cross-sectional views of core particles (102A-102C) that may be included in the active material particle (100) of FIG. 1a. Referring to FIG. 1a and 1b, the active material particle (100) comprises a core particle (102) containing an electrochemically active material and a graphene-containing coating (110) coated on and / or encapsulated on the core particle (102).

[0024] In a preferred embodiment, the core particle (102) comprises an M-SiO material. As such, the active material particle (100) is described below in relation to the core particle (102) comprising the M-SiO material. The active material particle (100) and / or the core particle (102) may have an average particle size in the range of about 1 μm to about 20 μm, e.g., about 2 μm to about 15 μm, about 3 μm to about 10 μm, about 3 μm to about 7 μm, or about 5 μm. The core particle (102) may comprise an M-SiO material comprising metallated silicon chemical species and silicon (e.g., crystalline and / or amorphous silicon). The metallated silicon species may include metallated silicides and metallated silicates. In some embodiments, the M-SiO material also comprises silicon oxide (SiO₂). x , where x may include a range of 0.8 to 1.2, such as 0.9 to 1.1. In various embodiments, the M-SiO material may include lithiated silicon species. Here, "lithiated silicon species" refers to lithium silicide (Li x Si, 0 <x<4.4) 및 / 또는 하나 이상의 리튬 실리케이트(Li2Si2O5, Li2SiO3및 / 또는 Li4SiO4등)를 포함할 수 있다.

[0025] Referring to FIG. 1b, in some embodiments, the active material particle (100) may comprise a heterogeneous core particle (102A) comprising an M-SiO material comprising a plurality of silicon-containing material phases (104, 106, 108). For example, the phases (104, 106, 108) may independently be crystalline silicon, silicon oxide (e.g., SiO). x, where x is in the range of 0.8 to 1.2, such as 0.9 to 1.1), and / or may include lithiated silicon species. However, in some embodiments, the core particle (102) may be a substantially homogeneous particle comprising silicon, oxygen, and lithium, without distinct phases.

[0026] Referring to FIG. 1c, in some embodiments, the active material particle (100) may comprise a core particle (102B) comprising a primary phase (120), and crystalline silicon domains (122) are dispersed in the primary phase as a secondary phase. For example, the primary phase (120) may comprise a lithium silicate species, particularly a lithiated silicon species such as Li2Si2O5. In other embodiments, the primary phase (120) may comprise a magnesium metallated silicon species, such as a magnesium silicate species, particularly MgSiO3, Mg2SiO4, or combinations thereof. The crystalline silicon domains (122) may comprise crystalline silicon nanoparticles having a particle size of less than 100 nm. For example, the crystalline silicon domains (122) may have an average particle size in the range of about 3 nm to about 60 nm. In one embodiment, most of the crystalline silicon domains (122) may have an average particle size in the range of about 5 nm to about 10 nm, and the remaining crystalline silicon domains (122) may have an average particle size in the range of about 10 nm to about 50 nm.

[0027] Referring to FIG. 1d, in some embodiments, the active material particle (100) comprises: a primary phase (120) containing an M-SiO material, a crystalline silicon domain (122), and SiO x Domain (124) (e.g., SiO x, where x is in the range of 0.8 to 1.2, e.g., 0.9 to 1.1), may be included as a secondary phase dispersed in the primary phase (120). For example, the primary phase (120) may include a lithium silicate species, particularly a lithiated silicon species such as Li2Si2O5, and the crystalline silicon domain (122) may include crystalline silicon nanoparticles, and SiO x The domain (124) is SiO x It may include phases and / or nanoparticles. Crystalline silicon domains (122) and SiO x The domain (124) may have a particle size of less than about 100 nm. For example, a crystalline silicon domain (122) and SiO x The domain (124) may have an average particle size in the range of about 3 nm to about 60 nm, such as about 5 nm to about 50 nm.

[0028] In various embodiments, the core particle (102) may comprise about 90% to 95% by weight of the total weight of the active material particle (100), and may represent about 80% to about 99.5% by weight, e.g., about 90% to about 99% by weight. In some embodiments, the M-SiO material may comprise: about 40% (at%) to about 5% by weight, e.g., 20% to about 10% by weight, or about 15% by weight of lithiated silicon species. In some embodiments, the M-SiO material of the core particle (102A) may comprise: about 60% to about 95% by weight, e.g., about 80% to about 90% by weight, or about 85% by weight of silicon and SiO. x It may include. The M-SiO material of the core particle (102) may have a silicon-to-oxygen atomic weight ratio in the range of about 1.25:1 to about 1:1.25, e.g., about 1.1:1 to about 1:1.1, or about 1:1. In some embodiments, the M-SiO material of the core particle (102) is crystalline silicon and SiO of roughly equal atomic weights. xIt may include.

[0029] During the initial charging reaction and / or subsequent charging reaction, the composition of the M-SiO material of the core particle (102A) may change due to lithiation and / or other reactions. For example, Si and SiO x is lithiated Li x Si domains can be formed. In addition, some SiO x It can form inert species such as lithium silicate and Li2O.

[0030] In various embodiments, the coating (110) may be in the form of a shell that completely encapsulates the core particle (102), as illustrated in FIGS. 1b through 1d. However, in some embodiments, the coating (110) may only partially encapsulate some or all of the core particle (102). In some embodiments, the coating (110) may represent about 0.5% by weight to about 20% by weight, e.g., about 1% to about 10% by weight, or about 5% to about 10% by weight, based on the total weight of the active material particle.

[0031] turbostratic carbon

[0032] In some embodiments, the coating (110) may comprise a flexible, highly conductive graphene material, such as graphene, graphene oxide, partially reduced graphene oxide, or a combination thereof. For example, the coating (110) may comprise a flexible, highly conductive graphene material having low-defect, non-layered properties, which may preferably be referred to as non-layered carbon. The low-defect, non-layered carbon may be in the form of platelets comprising one to about 10 layers of a graphene material, such as graphene, graphene oxide, or reduced graphene oxide. In some embodiments, the low-defect, non-layered carbon may comprise at least 90 weight percent, for example, about 90 weight percent to about 100 weight percent of graphene. The graphene material may further comprise: powder, particles, single-layer sheets, multilayer sheets, flakes, plates, ribbons, quantum dots, tubes, fullerenes (hollow graphene spheres), or a combination thereof.

[0033] The nacreous carbon may be in the form of partially overlapping sheets or plates to simulate a single sheet structure of a larger size. In some embodiments, the plates have one or more layers of a graphene-based material. In some embodiments, the plates may have an average sheet size of < 15 μm. In some embodiments, the plates may have an average sheet size of 1 μm or less. In some embodiments, the nacreous carbon-based material plates may have a thin thickness. In some embodiments, the low thickness of the nacreous carbon-based material plates may be an average of 1 μm or less. In some embodiments, the low thickness of the nacreous carbon-based material plates may be an average of 100 nm or less.

[0034] In various embodiments, the coating (110) may be in the form of a shell that completely encapsulates the particle (100), as shown in FIG. 1b. However, in some embodiments, the coating (110) may partially encapsulate some or all of the active substance particle (100). In some embodiments, the coating (110) may represent about 0.5% to about 20% by weight of the total weight of the particle (100) and the coating (110), e.g., about 1% to about 10% by weight, or about 5% to about 10% by weight.

[0035] Due to its conductive properties, the coating (110) can ensure that the core particles (102) circulate homogeneously / uniformly in all three dimensions (movement of electrons and lithium ions into and out of the structure), thereby minimizing the applied stress and minimizing particle fragmentation by the core particles. Additionally, if the particles (100) are fragmented, the flexible coating (110) acts to electrically connect the fragmented silicon oxide material and maintain the overall integrity of the particles (100), thereby significantly improving electrochemical performance.

[0036] Figures 2a, 2b, and 2c show the Raman spectra for graphite and various graphene-based materials. Graphite and graphene materials are approximately 1340 cm⁻¹. -1 Wow, 1584 cm -1 Wow, 2650 cm -1 and 2750 cm -1 Between (e.g., about 2700 cm) -1 It is well known that it has a characteristic peak at 1340 cm⁻¹. -1 The peak at 1584 cm⁻¹ is shown in Fig. 2c and is characterized by the D band. -1 The peak at appears in the spectra of Figures 2a and 2c and is characterized by the G band, which is sp 2It originates from vibrational modes represented by the stretching of C=C bonds in all pairs of hybridized carbon atoms. The D band originates from hybrid vibrational modes associated with graphene edges and indicates defects or broken symmetry in the graphene structure. The 2D band is at 2650 cm⁻¹. -1 to 2750 cm -1 Peak intensity at wavenumbers between (I 2D It is characterized by ). 2700 cm -1 The peak at is illustrated in Fig. 2b and is characterized by a 2D band resulting from a double resonance process caused by interactions between stacked graphene layers. The appearance of a double peak at the 2D wavenumber breaks the symmetry of the peak and indicates an AB stacking order between the graphene plane of graphite and graphite derivatives such as nanoplatelets. The 2D1 peak illustrated in Fig. 1b is suppressed when the AB stacking order of the non-layered multilayer graphene particles is disrupted. The positions of the G and 2D bands are used to determine the number of layers in the material system. Thus, Raman spectroscopy provides scientific clarity and definition regarding electrochemical cell carbon material additives, thereby providing a fingerprint for the correct selection as an additive for active material electrode compositions. As will be shown, this definition provides a fingerprint for the low-defect non-layered carbon of this application. It is the low-defected non-layered carbon used as an additive in electrochemical cell electrode active material mixtures that provides excellent electrochemical cell performance.

[0037] FIG. 3 shows I of a carbon additive typically used in electrode active material mixtures (i.e., reduced graphene oxide or amorphous carbon) of the prior art, compared to the low-defect, non-layered carbon of the present application. D / I G Provides a ratio.

[0038] Reduced graphene oxide (rGO) is a carbon variant often referred to as graphene in the industry, but it is unique in its final structure and manufacturing process. Graphene oxide is typically first prepared using a modified Hummers method, in which the graphite material is oxidized and can be exfoliated into several layers of carbon-containing sheets or single layers containing various functional groups, including but not limited to hydroxyl, epoxide, carbonyl, and carboxyl groups. These functional groups are removed through chemical or thermal treatment that converts the insulating graphene oxide into conductive reduced graphene oxide. While reduced graphene oxide is similar to graphene in that it consists of a single-layer carbon atomic lattice, it differs in that it contains a mixture of sp2 and sp3 hybridization, has residual functional groups, and often exhibits increased defect density during the manufacturing and reduction processes. Reduced graphene oxide is shown in the first bar of Fig. 3 and I D / I G The ratio is 0.9.

[0039] Amorphous carbon is often used as an additive or surface coating for both anode and cathode material mixtures in electrochemical cells to improve electrode conductivity. Typically, amorphous carbon is produced using a chemical vapor deposition (CVD) process in which a hydrocarbon feedstock gas flows into a sealed container and carbonizes the surface of the desired powder material at an elevated temperature. This pyrolysis process can provide a thin amorphous carbon coating approximately a few nanometers thick, lacking any sp2 hybridization found in crystalline graphene-based materials. Amorphous carbon is shown in the third bar of Fig. 3 and I D / I G The ratio is >1.2.

[0040] Low-defect, non-layered carbon, also known as graphene, possesses unique characteristics resulting from the manufacturing process. One common method for producing this material is through a plasma-based CVD process in which a hydrocarbon feedstock gas is fed through an inert gas plasma in the presence of a catalyst capable of nucleating graphene-like carbon structures. By controlling production parameters, it is possible to produce carbon materials with several layers and no AB stacking order between the lattices. These carbon materials are typically highly ordered sp2 carbon lattices with low defect density.

[0041] The low-defect egg-shaped carbon of the present disclosure is illustrated in the central second bar of FIG. 3. The Raman spectrum of the low-defect egg-shaped carbon additive of the present application is the D band and the G band (I D / I G ) and the intensity ratio of the 2D band to the G band (I 2D / I G It is derived from ). I D , I 2D and I G is indicated by the respective integration strength. Low I D / I G The ratio indicates a material with few defects. The low-defect, non-straw carbon material of the present invention is 1580 to 1600 cm -1 I in the range of wavenumbers G Wow, 1330 to 1360 cm -1 I in the range of wavenumbers D Raman spectroscopy using and I measured using an incident laser wavelength of 532 nm D / I G The ratio is greater than 0 and less than or equal to about 0.8. In addition, the low-defect infertile carbon material of the present invention has an I of about 0.4 or higher. 2D / I G Represents a ratio. 2D / I G As a reference regarding the ratio, approximately 2's I 2D / I GThe ratio is generally associated with single-layer graphene. I of less than about 0.4 2D / I G The ratio is generally related to bulk graphite composed of multiple AB stacked graphene layers. Accordingly, for the low-defect, non-stacked carbon material of the present disclosure, an I of about 0.4 or more 2D / I G The ratio indicates a low number of layers < 10. Low-defect, non-layered carbon materials with a low number of layers lack the stacking order AB between graphene layers (i.e., non-layered). This non-layered characteristic of the graphene plane or the defect in AB stacking is I 2D It is indicated by the symmetry of the peaks. Distinguishing between irregularly stacked graphene materials and AB-stacked graphene materials is the symmetry of the 2D peaks, which indicates the stacking order forming the layers versus rotational stacking disorder.

[0042] Carbon materials with a high AB stacking order still exhibit 2D peaks, but these 2D peaks display doublets that break the symmetry of the peaks. This symmetry breaking occurs in both several-layer AB stacked graphene and many-layer graphite. Therefore, regardless of the number of graphene layers present in the material, the 2D peaks, which are a very strong indicator of the presence of stacking order, are important when selecting graphene or graphene-based additives. The rotational disorder of low-defect, non-stacked carbon stacking distinguishes it from all other graphene or graphene-based additives used to date, because the rotational disorder of the stacking in the low-defect, non-stacked carbon of the present application provides flexibility to the carbon-based particles of the present application, which enables these carbon-based particles within to provide and maintain contact with the active core particles of composite particles containing the electrodes of an electrochemical cell. As a result, an electrochemical cell with increased cycle life, improved cycle life stability, enhanced energy density, and excellent high-speed performance is produced.

[0043] Figures 4a through 4c illustrate Raman spectra for active material mixtures containing SiO particles encapsulated or coated with carbon materials. Figure 4a is a graph of the Raman spectrum for an active material mixture containing SiO core particles coated with amorphous carbon material. Figure 4b is a graph of the Raman spectrum for an active material mixture containing SiO core particles encapsulated by rGO. Figure 4c is a graph showing the Raman spectrum for an active material mixture containing core particles encapsulated by low-defection non-layered carbon. Each spectrum is at various layer thicknesses (wavelength 2700 cm⁻¹). -1 Size, shape, and position of surrounding 2D peaks) and disorder (wavelength 1340 cm⁻¹ -1 It differs due to the size of the surrounding D peak.

[0044] Raman analysis sample preparation involves taking small amounts of powders, such as active material powder, complex material powder, or carbon material powder, and placing them individually into clean glass vials. The sample powders are rinsed with methanol. Then, the powder / methanol solution is briefly vortexed and sonicated for approximately 10 minutes. Subsequently, the suspension is transferred to a microscope slide using a micropipette. The slide is then completely air-dried before performing the analysis.

[0045] The Raman spectroscopic analysis of this application is performed using confocal Raman spectroscopy on a Bruker Senterra Raman System under the following test conditions: 532 nm laser, 0.02 mW, 50X objective lens, 90 sec integration time, three additional cavities (three Raman spectroscopic sample runs), 50 x 1000 μm aperture, and 9 to 18 cm. -1Use of resolution. For reference, the D band is not activated in Raman scattering of perfect crystals. The D band becomes Raman active in defective graphite materials due to defect-induced double resonance Raman scattering processes involving π-π electronic transitions. Compared to the G band, the intensity of the D band increases with the amount of disorder. Therefore, intensity I D / I G The ratio can be used to characterize graphene materials.

[0046] The D and G bands of amorphous carbon shown in Fig. 4a both have higher intensities than the D and G bands of reduced graphene oxide (rGO) in Fig. 4b, or the D and G bands of torn-layer carbon in Fig. 4c. Amorphous carbon also has substantially higher I than rGO and torn-layer carbon. D / I G It shows a ratio (1.25). The suppressed intensity of the amorphous carbon G band compared to the D band reflects the lack of crystallinity (also called graphite properties) within the carbon structure. The fact that the D peak intensity is higher than the G peak intensity is due to the large amount of defects in the amorphous carbon network. Therefore, the amorphous carbon spectrum exhibits lower crystallinity and much higher disorder in the graphite network compared to more crystalline carbon, such as graphene, graphene oxide, and rGO. Additionally, the intensity of the rGO D peak is higher compared to the G peak, and I compared to the intensities of the amorphous carbon D and G peaks. D / I G Rain is higher (almost twice as much), and the above I D / I G The ratio indicates that rGO has more defects than the layered carbon of the present application.

[0047] Table 1 below provides details regarding the Raman spectra of Figures 4a to 4c.

[0048] [Table 1]

[0049]

[0050] Careful examination of these spectra reveals that as disorder increases, the D band broadens and the relative intensity of the band changes. For the amorphous carbon coated sample, the high intensity (6194.8) and broad D peak indicate a large amount of defects. The G peak (4908.2), which has a lower intensity than the D peak (6194.8), indicates a lack of crystallinity. The D peak intensity (9115.5) and G peak intensity (10033.3) of the rGO encapsulated sample are quite similar. However, it is noteworthy that the D peak intensity (9115.5) of the rGO sample is substantially higher than that of the pyroclastic carbon sample (2915.3), indicating that the rGO sample has a substantially higher defect density than the pyroclastic carbon sample. Additionally, the G bands of the amorphous carbon and rGO samples are at a wavelength of 1584 cm⁻¹, respectively. -1 At a wavelength of 1589.4 cm -1 and 1597.82 cm -1 While shifted to the right, the G band of the egg-strand carbon sample is 1581.32 cm⁻¹ -1 From 1584 cm -1 It is positioned slightly to the left with respect to the wavelength. Importantly, unlike amorphous carbon and rGO samples, the nymphatic carbon (in this case, the graphene sample) exhibits almost no positional displacement and thus has few defects; therefore, it is nearly similar to an 'perfect' nymphatic carbon material.

[0051] electrode material

[0052] Various embodiments of the present disclosure provide electrode materials for lithium-ion batteries, particularly anode electrode compositions. As illustrated in FIG. 5a, the electrode material may comprise an active material, a binder (not shown), and single-walled carbon nanotubes (SWCNTs; 120). The active material may comprise the aforementioned active material particles (100) and optionally additional graphite particles (130). In some embodiments, the electrode material may optionally comprise a conductive additive such as carbon black particles (140). The active material particles (100) and the graphite particles (130) may be mixed with each other. The carbon black particles (140) may be smaller than the active material particles (100) and the graphite particles (130) (i.e., have a smaller diameter) and may be located between (130) and / or on the surfaces thereof of the active material particles (100) and / or the graphite particles. SWCNT (120) can be extended between a mixture of active material particles (100) and graphite particles (130) and can provide long-distance conductivity over a number of active particles (100, 130).

[0053] As illustrated in FIG. 5b, after a number of charge and discharge cycles, the silicon oxide particles (100) and graphite particles (130) can swell and repel each other. However, because the SWCNT (120) is long and has a high aspect ratio, it still contacts and electrically connects a number of active material particles (100) and graphite particles (130). Thus, the SWCNT (120) is believed to provide a permeation network of conductive links between active particles (e.g., a web or mesh exceeding a permeation threshold) that provides sufficient conductivity to the anode electrode.

[0054] The electrode material may contain an active material in an amount of 80 wt% or more, e.g. 90 wt% or more, 94 wt% or more, e.g. 90 to 96.5 wt%. The active material may comprise a mixture of active material particles (100) and optionally graphite particles (130). For example, the active material may comprise: about 5 wt% to about 50 wt%, e.g. about 10 wt% to about 30 wt%, about 15 wt% to about 25 wt% of M-SiO, and about 95 wt% to about 50 wt%, e.g. about 90 wt% to about 70 wt%, or about 85 wt% to about 75 wt% of graphite. In some preferred embodiments, the active material may comprise less than 50 wt% of M-SiO and more than 50 wt% of graphite. Thus, the active material may comprise graphite particles (130) in a greater weight than the active material particles (100).

[0055] The active material particle (100) may include silicon and metal silicate phases, and optionally may include the aforementioned silicon oxide phase. The active material particle (100) may include any carbon coating (110), or the carbon coating (110) may be omitted.

[0056] The average particle size of the active material particles (100) may be: about 1 µm to about 20 µm, e.g., about 1 µm to about 10 µm, about 3 µm to about 7 µm, or about 5 µm. The active material particles (100) are about 0.5 m 2 / g to about 30 m 2 / g, for example, about 1 m 2 / g to about 20 m 2 / g, about 5 m 2 / g to about 15 m 2 It can have a surface area in the range of / g.

[0057] The graphite may comprise graphite particles (130) of synthetic or natural origin. The graphite may have an average particle size in the range of about 2 µm to about 30 µm, such as about 10 µm to about 20 µm, including about 12 µm to about 18 µm. In one embodiment, the average particle size of the graphite particles (130) may be larger than the average particle size of the silicon oxide particles (100). The graphite particles (130) are about 0.5 m 2 / g to about 2.5 m 2 / g, for example, about 1 m 2 / g to about 2 m 2 It can have a surface area in the range of / g. The graphite particles (130) can be larger than the silicon oxide particles (110).

[0058] The electrode material may include any suitable electrode material binder (not shown in FIG. 5a and 5b for clarity). For example, the electrode material may include a polymeric binder such as polyvinylidene difluoride (PVDF), Na-carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (LiPAA), or a combination thereof. In some embodiments, the binder may include a combination of CMC and SBR, wherein the CMC has a molecular weight of 250 to 850 g / mol and a degree of substitution of 0.65 to 0.9.

[0059] In various embodiments, the electrode material may comprise about 1 weight% to about 5 weight%, or about 2 weight% to about 3 weight% of a binder.

[0060] SWCNT (120) may have an average length of about 1 μm or more. For example, SWCNT may have an average length in the range of about 1 μm to about 500 μm, e.g., about 1 μm to about 10 μm. SWCNT may have an average diameter in the range of about 0.5 nm to about 2.5 nm, e.g., about 1 nm to about 2 nm.

[0061] SWCNT (120) has an I of about 5 or more, for example about 6 or more or about 10 or more, as determined by Raman spectroscopy. G / I D It can have a ratio, and as measured using an incident laser wavelength of 633 nm, I G is wavenumber 1580 to 1600 cm -1 It is related to the Raman intensity of, and I D The wavenumber is 1330 to 1360 cm -1 It is related to the Raman intensity.

[0062] In various embodiments, the electrode material may comprise SWCTNs of about 0.05 wt% to about 1 wt%, e.g., about 0.075 wt% to about 0.9 wt%, about 0.08 wt% to about 0.25 wt%, or about 0.1 wt%.

[0063] A conductive additive (i.e., a conductive aid) may include: carbon black (e.g., KETJENBLACK or Super-P carbon black), low-defect non-layer carbon, acetylene black, channel black, furnace black, lamp black, thermal black, or a combination thereof. The conductive additive may optionally include: metal powder, fluorocarbon powder, aluminum powder, nickel powder, nickel flakes, conductive whiskers, zinc oxide whiskers, potassium titanate whiskers, conductive metal oxides, titanium oxide, conductive organic compounds, conductive polyphenylene derivatives, conductive polymers, or a combination thereof.

[0064] In various embodiments, the electrode material may comprise a conductive additive (i.e., a conductive agent) in an amount of 0 to 5 wt%, such as 0.1 wt% to 5 wt%, 0.5 wt% to 1.5 wt%, or 1 wt%, such as 0.25 wt% to 3 wt%, and said conductive additive is selected from carbon black, an electrically conductive polymer, a metal powder, or any combination thereof. In some embodiments, the conductive additive may preferably comprise carbon black.

[0065] Anode formation

[0066] According to various embodiments, the anode may be formed using any suitable method known to those skilled in the art. For example, the aforementioned active material particles (100) may be mixed with graphite particles (130) to form an active material. In one embodiment, the active material may comprise less than 50 weight% M-SiO and more than 50 weight% graphite. The active material may be mixed with SWCNTs, a binder, and an optional conductive additive to form a solid component. In some embodiments, the active material particles may be coated with a non-layered carbon coating (110), for example using a spray drying process, before forming the active material. Alternatively, the coating (110) may be omitted.

[0067] The solid component may be mixed with a polar solvent, such as water or N-methyl-2-pyrrolidone (NMP), in an amount of about 20 to 60 weight percent solid loading to form an electrode slurry. For example, mixing may include performing the mixing under vacuum using a planetary mixer and a high-shear dispersion blade.

[0068] Then, the electrode slurry can be coated onto a metal substrate, for example, a copper or stainless steel substrate, with an appropriate mass load to balance the lithium capacity of the anode and the lithium capacity of the selected cathode. The coating can be performed using various devices, such as a doctor blade, a comma coater, a gravure coater, a slot die coater, etc.

[0069] After coating, the slurry can be dried to form an anode. For example, the slurry can be dried under forced air at a temperature ranging from room temperature to about 120°C. The dried slurry can be compressed to reduce internal porosity, and the electrode can be cut into a desired shape. A typical anode compression density can be in the range of about 1.0 g / cc to about 1.7 g / cc, depending on the electrode composition and target application. A cathode compression density can be in the range of about 2.7 to about 4.7 g / cc.

[0070] In some embodiments, the active material particles may be coated with infrasoil carbon before forming the active material. For example, a mixture of the active material particles, infrasoil carbon, and a solvent may be spray-dried to form a powder, and then the powder may be heat-treated in an inert atmosphere, such as argon gas, to carbonize any remaining surfactant or dispersant. In other embodiments, the active material particles may be coated with infrasoil carbon using a binder and a mechanical fusion process.

[0071] Electrochemical cell assembly

[0072] The configuration of the electrochemical cell comprises a pair of coated anode substrates and coated cathode substrates that are electronically separated from each other by polymer and / or ceramic electrical insulating separators. The electrode assembly is sealed in a housing that may be of various structures, such as but not limited to coin cells, pouch cells, or can cells, and comprises a non-aqueous ion-conducting electrolyte operably coupled to the anode and cathode. The electrolyte consists of an inorganic salt dissolved in a non-aqueous solvent, and more preferably, an alkali metal salt dissolved in a mixture of a low-viscosity solvent comprising organic esters, ethers, and dialkyl carbonates, and a high-conductivity solvent comprising cyclic carbonates, cyclic esters, and cyclic amides. Non-limiting examples of electrolytes may include lithium hexafluorophosphate (LiPF6) or lithium bis(fluorosulfonyl)imide (LiFSi) salts in an organic solvent comprising one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), or a combination thereof.

[0073] Additional solvents useful for embodiments of the present invention include: dialkyl carbonates, e.g., tetrahydrofuran (THF), methyl acetate (MA), diglyme, trigylme, tetragylme, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), 1-ethoxy,2-methoxyethane (EME), ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and combinations thereof. In addition, high dielectric constant solvents that may be useful include: cyclic carbonates, cyclic esters and cyclic amides, such as propylene carbonate (PC), butylene carbonate, acetonitrile, dimethyl sulfoxide, dimethyl formamide, dimethyl acetamide, gamma-valerolactone, gamma-butyrolactone (GBL), N-methyl-2-pyrrolidone (NMP), and combinations thereof.

[0074] The electrolyte may also include one or more additives, such as vinylene carbonate (VC), 1,3-propanesulfone (PS), propane-1-en-1,3-sulfone (PES), fluoroethylene carbonate (FEC) and / or propylene carbonate (PC). The electrolyte acts as a medium for the movement of lithium ions between the anode and the cathode during the electrochemical reaction of the battery, particularly during the discharge and recharging of the battery. The electrochemical cell may also have a positive terminal and a negative terminal and / or contact structure.

[0075] Experimental Example

[0076] The following examples relate to an anode formed using electrode materials of various embodiments of the present disclosure and electrode materials of comparative examples, and are provided as examples without limitation. In the examples, % is weight%, g is grams, CE is Coulomb efficiency, and mAh / g is capacity.

[0077] Exemplary battery 1-3 (E1, E2, E3)

[0078] A solid component was formed by mixing SWCNTs as an active material, a conductor (carbon black), and a binder (CMC / SBR). The solid component was mixed with a polar solvent (water or NMP) in a planetary mixer equipped with high-shear dispersion blades in a vacuum at a solid load of 20% to 60% to form an electrode material slurry.

[0079] An electrode material slurry was coated onto a copper current collector with an appropriate mass loading to balance the lithium capacity of the anode and the lithium capacity of the selected cathode, dried, and pressed to form an anode. The anode was assembled into a half cell (excess counter electrode material = lithium metal), and an electrolyte was provided to each half cell to form exemplary cells 1 to 3. The anodes of exemplary cells 1 to 3 each contained 96 wt% active material, 0.1 wt% SWCNT, 0.9 wt% carbon black, and 3 wt% CMC / SBR binder.

[0080] The anode of exemplary cell 1 contained 20 wt% LM-SiO and 76 wt% graphite. The anode of exemplary cell 2 contained 30 wt% LM-SiO and 66 wt% graphite. The anode of exemplary cell 3 contained 30 wt% non-metallic SiO and 66 wt% graphite.

[0081] Comparative Example Batteries 1 to 4 (C1, C2, C3, C4)

[0082] Comparative example cells 1 to 4 were formed in the same manner as exemplary cells 1 to 3. The anode of Comparative Example Cell 1 contained 20 wt% LM-SiO, 76 wt% graphite, and 1 wt% carbon black, and did not contain CNTs. The anode of Comparative Example Cell 2 contained 30 wt% LM-SiO, 66 wt% graphite, 0.9 wt% carbon black, and 0.1 wt% multi-walled carbon nanotubes (MWCNTs).

[0083] The anode of Comparative Example Cell 3 comprises 30 wt% LM-SiO, 66 wt% graphite, and 1 wt% carbon black, and does not contain CNTs. The anode of Comparative Example Cell 4 comprises 30 wt% non-metallic SiO, 66 wt% graphite, and 1 wt% carbon black, and does not contain CNTs.

[0084] Table 2 below shows the half-cell cycling protocols applied to the exemplary cell and the comparative example cell.

[0085] [Table 2]

[0086]

[0087] Figure 6a is a graph showing the specific capacity retention of Example Cell 1 and Comparative Example Cell 1 during cycling. As can be seen in Figure 6a, Example Cell 1 containing SWCNT had excellent capacity retention for 100 cycles. In contrast, Comparative Example Cell 1 not containing SWCNT lost more than 50% of its initial capacity in less than 20 cycles.

[0088] Figure 6b is a graph showing the capacity retention of Example Cell 2 and Comparative Examples Cells 2 and 3 during cycling. As can be seen in Figure 6b, Example Cell 2, containing SWCNT, had excellent capacity retention. In contrast, Comparative Examples Cells 2 and 3, containing MWCNT or not containing CNT, respectively, exhibited a capacity loss of more than 50% in less than 10 cycles.

[0089] Figure 6c is a graph showing the capacity retention of Example Cell 3 and Comparative Example Cell 4 during cycling. As can be seen in Figure 6c, Example Cell 3, which contains SWCNT and non-metallic SiO instead of LM-SiO, exhibited excellent capacity retention. In contrast, Comparative Example Cell 4, which contains non-metallic SiO and does not contain CNT, showed a capacity loss of approximately 50% after 10 cycles.

[0090] Therefore, the mixture of SWCNT with M-SiO and graphite improves the Coulomb efficiency and cycle life of the silicon anode by buffering the volume change of silicon particles during charging / discharging, and reduces the measurable expansion of the electrode. The addition of SWCNT to the electrode composition provides relatively long-distance conductivity across multiple electrode particles that are flexible enough to maintain a conductive network when the electrode particles swell. As a result, capacity retention is improved as the lithium-ion battery / electrode charges and discharges during operation.

[0091] The long-range conductivity provided by SWCNTs enables unexpectedly higher loading of high-capacity alloy active materials, preventing capacity degradation through electrical isolation despite more severe overall electrode expansion.

[0092] The addition of SWCNTs can also reduce the total carbon black content added for electrical conductivity, which consequently reduces the amount of polymer binder added for mechanical integrity and the total surface area of ​​the electrode. Furthermore, carbon black is a nanomaterial that blocks pores by occupying the interstitial space between the active materials that store lithium. High concentrations of carbon black are undesirable because they prevent proper calendering (compression) of the electrode. The reduction in binder content and the increase in constant density provide significant advantages in activated high-energy-density lithium-ion batteries.

[0093] It will be understood that while the foregoing describes specific preferred embodiments, the present invention is not limited thereto. It will be obvious to those skilled in the art that various modifications may be made to the disclosed embodiments, and that such modifications are intended to be within the scope of the present invention. All publications, patent applications, and patent publications cited herein are incorporated herein by reference in their entirety.

Claims

Claim 1 An electrode material for a lithium-ion secondary battery comprises: active material particles comprising an alkali metal or alkaline earth metal silicate; a binder; and single-walled carbon nanotubes (SWCNTs); wherein the active material particles comprise a coating comprising pyroplastic carbon having a Raman spectrum measured using an incident laser wavelength of 532 nm, and the Raman spectrum is: 1330 cm⁻¹ -1 and 1360 cm -1 Peak intensity (I) at wavenumbers between D D band having ); 1580 cm -1 and 1600 cm -1 Peak intensity (I) at wavenumbers between G G band having ); and 2650 cm -1 and 2750 cm -1 Peak intensity (I) at wavenumbers between 2D Having a 2D band with ), and I D / I G The ratio of is greater than 0 and in the range of 1.1 or less; I 2D / I G Electrode material for a lithium-ion secondary battery, wherein the ratio is in the range of 1.03 to 2. Claim 2 An electrode material for a lithium-ion secondary battery according to claim 1, wherein the electrode material comprises, based on the total weight of the electrode material: a combination of graphite particles and active material particles of at least 80 weight%; 1 weight% to 5 weight% of a binder; and 0.05 weight% to 1 weight% of single-walled carbon nanotubes (SWCNT). Claim 3 In paragraph 2, the SWCNT is an electrode material for a lithium-ion secondary battery having an average diameter in the range of 0.5 nm to 2.5 nm and an average length greater than 1 μm. Claim 4 In paragraph 3, the SWCNT is: 5 or more I determined by Raman spectroscopy G / I D An electrode material for a lithium-ion secondary battery having a ratio and an average length in the range of 10 μm to 500 μm; the electrode material comprises: 0.08 wt% to 0.25 wt% of SWCNT. Claim 5 In paragraph 2, the electrode material comprises: a combination of 90 weight% to 96.5 weight% of graphite particles and active material particles, an electrode material for a lithium-ion secondary battery. Claim 6 An electrode material for a lithium-ion secondary battery according to claim 5, wherein the electrode material comprises: 50% to 95% by weight of graphite particles; and 5% to 50% by weight of active material particles. Claim 7 An electrode material for a lithium-ion secondary battery according to claim 6, wherein the electrode material comprises: 70% to 90% by weight of graphite particles; and 10% to 30% by weight of active material particles. Claim 8 In claim 6, the graphite particles have an average particle size in the range of 2 μm to 30 μm and 0.5 m 2 / g to 2.5 m 2 Having a surface area in the range of / g; the active material particles have an average particle size in the range of 1 μm to 20 μm and 0.5 m 2 / g to 30 m 2 Electrode material for a lithium-ion secondary battery having a surface area of ​​ / g; wherein the graphite particles have an average particle size larger than that of the active material particles. Claim 9 An electrode material for a lithium-ion secondary battery according to claim 2, wherein the active material particles comprise: a primary phase comprising Li2Si2O5, Li2SiO3, Li4SiO4, or a combination thereof; and crystalline silicon domains dispersed in the primary phase. Claim 10 In claim 9, the active material particles are SiO dispersed within the primary phase. x An electrode material for a lithium-ion secondary battery, comprising additional domains, wherein x is 0.8 to 1.

2. Claim 11 An electrode material for a lithium-ion secondary battery according to claim 9, wherein the primary phase comprises Li2Si2O5; and the crystalline silicon domain has an average particle size of less than 100 nm. Claim 12 An electrode material for a lithium-ion secondary battery according to claim 2, wherein the active material particles comprise: a primary phase comprising MgSiO3, Mg2SiO4, or a combination thereof; and crystalline silicon domains dispersed in the primary phase. Claim 13 An electrode material for a lithium-ion secondary battery according to claim 2, wherein the binder comprises: polyvinylidene difluoride (PVDF), Na-carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (LiPAA), or a combination thereof. Claim 14 In paragraph 13, the above binder comprises a combination of CMC and SBR, an electrode material for a lithium-ion secondary battery. Claim 15 An electrode material for a lithium-ion secondary battery according to claim 2, wherein the electrode material further comprises 0.1% to 5% by weight of a conductive agent selected from carbon black, an electrically conductive polymer, a metal powder, or a combination thereof. Claim 16 In claim 15, the conductive aid comprises: carbon black powder having an average particle size smaller than the average particle size of the active material particles and graphite particles, an electrode material for a lithium-ion secondary battery. Claim 17 In claim 1, the SWCNT is an electrode material for a lithium-ion secondary battery that forms a percolating network of conductive links between the active material particles. Claim 18 In paragraph 1, the above I D / I G The ratio of is 0.8, and the above I 2D / I G Electrode material for a lithium-ion secondary battery, the ratio of which is 1.

03. Claim 19 A lithium secondary battery comprising: an anode including the electrode material of claim 1; a separator; a cathode; and an electrolyte disposed between the anode and the cathode. Claim 20 In claim 19, the SWCNT is a lithium secondary battery that reduces the electrical disconnection of active material particles during charging and discharging of the lithium secondary battery.

Citation Information

Patent Citations

  • Negative electrode piece and lithium-ion battery containing the same

    CN109950510A

  • Electrode active material-carbon nanotube composite and manufacturing method thereof

    JP2017084759A

  • Negative electrode active material, method for preparing the negative electrode active material, negative electrode comprising the negative electrode active material, and lithium secondarty battery comprising the negative electrode

    KR1020190092311A